Fixed-dose combination of calcipotriene/betamethasone dipropionate foam for the management of mild-to-moderate psoriasis in daily clinical practice: a collection of clinical experiences - Anna Campanati; Maria Esposito; Giacomo Caldarola; Sara Cacciapuoti; Gabriella Fabbrocini (BioExcel Publishing Ltd, 2024)
A fixed-dose combination of calcipotriene 0.005%/betamethasone dipropionate 0.064% (Cal/BD) aerosol foam (Enstilar, LEO Pharma) is the only topical therapy approved for the acute (reactive) and proactive management of psoriasis. Although treatment with Cal/BD foam has been characterized in a clinical context, further evidence is needed to determine its optimal use in clinical practice. A group of experts discussed the value of the Cal/BD foam as a topical treatment for mild-to-moderate psoriasis in combination with systemic treatments. The reported experiences support effectiveness of the Cal/BD foam in daily clinical practice, with an improvement in patient quality of life.